Arah Pembaruan Hukum Pidana Indonesia Pasca Perundangan Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana - Jamal Tubagus; Erwin Taroreh; Yusran Maaroef (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2027)
This article discusses the factors behind and the implications of the enactment of the new Criminal Code (KUHP) for criminal law reform in Indonesia. The method used is normative juridical legal research with a statutory approach and a conceptual approach. The results show that Indonesia's criminal law reform is directed toward decolonization of the law, strengthening Pancasila values, modernization of the sentencing system, strengthening human rights protection, restorative justice, and responses to technological developments and globalization. Law Number 1 of 2023 concerning the new Criminal Code is introducing a new paradigm in criminal sanctions. The research concludes that the success of criminal law reform requires the readiness of the entire criminal justice sub-system comprehensively, from implementing regulations, human resources, and infrastructure, to public awareness.